Yakut book culture at the All-Russia Baikal Forum. (A review) - S. Boitunova I.; С. Бойтунова И. (Scientific and Technical Libraries, 2020)
The article highlights the content of reports presented at the All-Russian Scientific and Practical Conference "National Libraries of the Subjects of the Russian Federation: Traditions and New Strategic Initiatives" (July 11-13, 2019 in Ulan-Ude). The purpose of the conference was to discuss and comprehend the significance of the National Library of the subject of the Russian Federation in preserving and disseminating the documentary cultural heritage of the peoples of Russia, ways of further developing public libraries as the most important resource for the spiritual development of modern society.The conference was organized by the Ministry of Culture of the Republic of Buryatia, the Ministry of Culture and Spiritual Development of the Republic of Sakha (Yakutia), the National Library of the Republic of Buryatia, the National Library of the Republic of Sakha (Yakutia), the East Siberian State Institute of Culture and the Arctic State Institute of Culture and Arts.The main attention is paid to the analysis of the distribution of the book in Yakutia in 1836-1917, as one of the leading areas of research activity of the National Library of the Republic of Sakha (Yakutia). The information on the distribution of the book in Yakutia, major implemented projects confirming the status of the National Library as a leading scientific center in the field of book science, library science and bibliography are presented. In addition to the main topic of the report, the library community was acquainted with the history, theory and modern practice of librarianship, the disclosure of funds, the study of book monuments in the region. В кратком обзоре освещена работа Байкальского форума 2019 г. – Всероссийской научно-практической конференции «Национальные библиотеки субъектов Российской Федерации: традиции и новые стратегические инициативы» (11–13 июля 2019 г., г. Улан-Удэ). Цель этого форума – обсудить и осмыслить значимость национальной библиотеки субъекта Российской Федерации в сохранении и распространении документного культурного наследия народов России, пути активизации деятельности общедоступных библиотек как важнейшего ресурса духовного развития современного общества. Организаторами конференции выступили Министерство культуры Республики Бурятия, Министерство культуры и духовного развития Республики Саха (Якутия), национальные библиотеки Республики Бурятия и Республики Саха (Якутия), Восточно-Сибирский государственный институт культуры и Арктический государственный институт культуры и искусств. Основное внимание в обзоре уделено анализу распространения книги в Якутии в 1836–1917 гг. как одному из ведущих направлений научно-исследовательской деятельности Национальной библиотеки Республики Саха (Якутия). Представлены сведения о распространении книги в Якутии, крупные реализованные проекты, подтверждающие статус национальной библиотеки как ведущего научного центра в области книговедения, библиотековедения и библиографии.